An annotated bibliography of C. C. Uhlenbeck’s writings on Basque (1888-1981) - Bakker, Peter; Hinrichs, Jan Paul (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
This bibliography aims at presenting all of C. C. Uhlenbeck’s publications on all aspects of the Basque language and the Basques in chronological order, including translations. The bibliography lists close to 100 items. Not all publications deal exclusively with Basque. We have also listed publications in which Basque is discussed in a wider context.